Fog and coffee: a new species of Tridimeris (Annonaceae) endemic to the mountain cloud forest of Mexico - Ortiz Rodríguez, Andrés Ernesto; Marinero-Sobal, Esteban José (Phytotaxa, 2022)
Tridimeris is the only genus of Annonaceae endemic to Mexico. Despite this, the genus has been largely ignored and very little is known about it; specifically its diversity and distribution in Mexico are not well studied. Here a new species of Tridimeris, T. huatuscoana, is described and illustrated. The most general characteristics of the new species confirm that dimerous flowers (two sepals and four petals) and the large, and fleshy fruits are the most obvious synapomorphies for the Mexican genus Tridimeris. With respect to the other two species described so far (Tridimeris hahniana and T. chiapensis), the new species can be easily distinguished by the unique combination of 2-flowered inflorescences, large petals pubescent outside, food bodies present at the base of its inner petals, setose leaf domatia, and fruits shortly pedunculate and stipitate. The new species expands the richness of the genus to three species, all endemic to Mexico and restricted to montane cloud forests.